Evidence-based preschool-age vision screening: health policy considerations - Deena Rachel Zimmerman; Hadas Ben-Eli; Bruce Moore; Monique Toledano; Chen Stein-Zamir; Ariela Gordon-Shaag (BMC, 2019)
Abstract Background There are many causes of visual impairment, and even blindness, which are treatable or at least preventable. Two such conditions are strabismus (crossed-eye, squint) and refractive error (visual image not focused on the most sensitive part of the retina). If these are not detected and corrected at an early age, they can lead to an irreversible impairment known as amblyopia (lazy eye). Pediatric vision screening and subsequent treatment for amblyopia and amblyogenic risk factors are thus key to preventing vision loss. Furthermore, vision screening can detect moderate to high hyperopia, which has been found to be associated with poor school readiness. Evidence-based recommendations call for screening children at 3-5 years of age; they are old enough to cooperate, but still within the window of effective intervention. However, these recommendations have yet to be universally implemented as the standard of care. Methods This paper integrates a review of the literature and the international experience of preschool vision screening with the findings from a preliminary feasibility study of expanded screening in Israel to formulate a discussion of the current health policy challenge in Israel and the options for addressing it. The advantages and disadvantages of various venues for vision screening are discussed. Findings Screening by optometrists in Mother and Child Health Centers, as implemented in a recent pilot project in the Jerusalem District, would allow the most comprehensive testing. Photo-screening in preschools would reach the most children, but at the cost of missing hyperopia (farsightedness). Either approach would probably constitute improvements over the current situation. The relative strengths of the two approaches depends in part on the ability to purchase automatic screening equipment (and the efficacy of that equipment) vs. the ongoing cost of paying trained personnel. Conclusions Further research should be conducted in Israel to determine the prevalence of refractive errors, so that best practices can be established for Israel's population and social needs. In the interim, the Ministry of Health should promptly implement the inclusion of preschool visions screening for children in the approved "basket of services" covered by the National Health Insurance Laws, using photo-screening, including collection of the clinical data.